(untitled) (Research, Society and Development, 2022)
The objective of this article is to analyze the adherence to self-care of men living with Diabetes Mellitus; and to help identify the main points that prevent men from non-adherence to treatment and self-care. This is an exploratory, descriptive research with a qualitative approach. Data collection occurred in the period from August to September 2021 through semi-structured interviews using a pre-established script, in a basic health unit in the city of Fortaleza - CE, which has a Specialized Center for Attention to the Diabetic and Hypertensive. Male diabetics were interviewed, with a total of 10 participants. From the analyzed data, the following categories were identified: Care, Change of habits and Feelings experienced after the diagnosis. It is expected that with these results it is possible to highlight the need to increase the presence of male patients in consultations and treatments, so that it is possible to mitigate the consequences caused by DM.